(untitled) (Third Sector Social Economic Review, 2025)
It is required to govern or control the external elements that come about as a result of the economic expansion that is accelerated by integration processes to ensure environmental sustainability. The ecological footprint, which is one of the environmental measuring indicators, is among the aspects that are investigated in this study. Other factors that are taken into consideration include economic growth, use of renewable energy, environmental taxation, and energy efficiency in Scandinavian nations from 1994 to 2020. Because of the diagnostic tests that were carried out, which included slope homogeneity tests and cross-sectional dependency tests, it was decided to utilize unit root tests of the second generation in the phase of the research that was devoted to analysis. The panel cointegration test was done to the variables that were determined to be stationary at the first level as a result of the second-generation unit root test. The results of this test led to the conclusion that the variables move together during the second generation. It is concluded, based on the findings of the panel quantile regression, that the increase in renewable energy has a negative impact on the ecological footprint at high quantile values, that environmental taxes have a negative impact on the ecological footprint with an increasing impact at high quantile values, and that energy efficiency has a more effective negative impact on the ecological footprint at medium quantiles. On the other hand, it is concluded that per capita income has a positive impact of increasing the ecological footprint. In conclusion, the results of the panel causality analysis indicate that there is a relationship of unidirectional causality between ecological footprint and per capita income, consumption of renewable energy, and environmental taxes. On the other hand, there is a relationship of bidirectional causality from ecological footprint to energy efficiency.